(Extended) Family Car, Filial Consumer-Citizens: Becoming Properly Middle Class in Post-Socialist South China. (January 2017) - Zhang, Jun
This article offers a glimpse into the mutually constructive process of the making of class, family, and state in a new material world. Relying on a decade of field research, I illustrate that a middle-class lifestyle in China, increasingly associated with a car, is deeply embedded in, and in turn reproduces, the multigenerational familial relationship contoured by state reproductive policies and the new political economy. Built upon the notions and practices of care and emotions, family values are at the core of the ethical conduct of being properly middle class. Yet, familial practices, unintentionally, resonate with the state agenda that seeks to reassert traditional values as a way to deal with an aging population and to establish its soft power on the global stage. The refocus on the family is not to deny the phenomenon of individualization, but rather to emphasize that it is merely part of the complex processes and assemblages in China's own trajectory toward modernity.